A modified boost rectifier for elimination of circulating current in power factor correction applications. (February 2017) - Venkitusamy, Karthikeyan; Padmanaban, Sanjeevikumar; Pecht, Michael; Awasthi, Abhishek; Selvamuthukumaran, Rajasekar
Abstract: This paper develops a modified AC/DC boost rectifier for power factor correction applications. The developed rectifier topology uses fewer devices compared to semi-bridgeless type boost rectifiers, and the overall efficiency is increased due to the elimination of the circulating current provided by the inductors. Moreover, it achieves a higher power factor and better total harmonic distortion (THD) in high load conditions. The performance of the developed topology was evaluated and verified by means of simulation and hardware experimental results. Highlights: This article exploited the elimination of circulating current by the developed new MBR compared to standard SBBR circuits. Proposed topology as reduced number of devices compared to standard SBBR circuits addressed in the literature. Losses are determined by theoretical background and confirmed with hardware prototype implementation of the developed MBR. Increased efficiency by the elimination of circulating current with minimum losses, high power factor and low THD output. Observed results shown good agreement with theory and suits electric vehicles, grid-connected and renewable energy sectors.